Effect of Temperature and Media on the Complexation of Sm(III) with 5-Bromo-2 Hydroxy Acetophenone - Ubale, Sanjay; PALASKAR, N.G.; Farooqui, Mazahar; Kotharar, Sandeep; Ubale, Milind (Asian Journal of Chemistry, 2010)
The present paper deals with the interaction of Sm(III) with 5- bromo-2-hydroxyacetophenone at different temperatures (30, 40, 50 and 60ºC). The stability constant of the complex has been studied in 25, 50 and 70% diozane-water mixture. pH-metric data based on Bjerrum Calvin method was employed for the calculation proton-ligand and metal-ligand stability constants. The systems were studied by maintaining M : L ratio 1 : 1 and 1 : 2.